University vice-chancellor pay, performance and (asymmetric) benchmarking - Adelina Gschwandtner; Richard McManus (University of Kent, School of Economics, 2018)
We study the pay of UK universities chief executives ("vice-chancellors") over a ten year period. Although there is a correlation between pay and performance, with better performing institutions paying higher salaries, we find limited evidence that this relationship is causal; that is, we find no statistically significant link that a change in pay leads to a change in performance, or vice-versa. Instead, we find strong support for an asymmetric benchmarking behaviour, where those institutions with below average pay increase their vice-chancellor's salaries quicker than those with above average pay. We simulate a model whereby different institutions target different places of the distribution of salaries and demonstrate that inflation of pay can be explained by this behaviour.
Keywords: G3; J33; Z13; 330; Executive Compensation; Performance Pay; Efficiency Wages; Benchmark